Evaluasi Penerapan CDOB sebagai Sistem Penjaminan Mutu pada Sejumlah PBF di Surabaya - VANNINA AGUSTINI; WAHYU UTAMI; WAHONO SUMARYONO; UMI ATHIYAH; ABDUL RAHEM (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Good Pharmaceutical Distribution Practice is called as CDOB in Indonesia is a guidelines to ensure pharmaceutical product quality throughout the distribution chain..This guideline consist of nine aspects, and pharmaceutical wholesalers (PBF) are required to implement the principle in the guideline as part of compliance to the pharmaceutical wholesaler regulation. The purpose of this research is to assess the extent of the implementation of Good Pharmaceutical Distribution Practices in the pharmaceutical daily operation.This research is descriptive with random sampling technique to determine which pharmaceutical wholesalers to be selected. The samples were 41 pharmaceutical wholesalers in Surabaya and they were given questionnaire they need to answer.. The data were collected in the period of August until September 2015, where the CDOB certifi cation was not mandatory yet. According to data collected, results show that 40 out of 41 (97.56%) PBF do not possessed CDOB certifi cate. From 41 PBFs, 18 (43.90%) PBF has met ≥80% CDOB, 16 (39.02%) PBF has met ≥65 - <80% CDOB, 6 (14.63%) PBF met ≥ 50 - <65% CDOB and 1 (2.44%) PBF met <50% CDOB. There was 1 (2.44%) PBF never conduct a study of the quality management, 4 (9.76%) offi cial pharmacist of respective PBF had never attended CDOB’s training and 5 (12.20%) PBF all their personnel have not been trained CDOB, 5 (12.20%) PBF never check the registration number, there are 2 (4.88%) PBF rarely keep the appropriate medication storage temperature indicated on the drug packaging.Overall, it may be said that not all the PBF in Surabaya implemented 9 aspects of CDOB. This could aff ect directly or indirectly to the quality of pharmaceutical products they distributed. CDOB certifi cation however, just became mandatory in November 2017.